THE PLACE AND ROLE OF NON-GOVERNMENTAL ACTORS IN POST-CONFLICT PEACEBUILDING IN UKRAINE - Литвин, О. Е. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The general theoretical approaches to the classification of actors in post-conflict peacebuilding, such as Lederach, Cambell and Hartnett, are analyzed, depending on approaches to understanding the concept of "post-conflict peacebuilding". The concepts of divided actors based on the region of work, the degree of their inclusion, the dominant sphere of activity and the nature of the methods used by the actors were considered. Attention is focused on the analysis of various approaches to the segregation of actors into specific clusters and their work within the conflict in Ukraine, according to regional peculiarities. The problems of the actors’ work are systematized and analyzed. The necessity of applying an integrated unifying classification of post-conflict peacebuilding actors is indicated to identify the most effective strategies for their interaction. Particular attention is paid to the adaptation of the classifications of actors to the modern context of the Ukrainian armed conflict. The role of non-governmental actors in the peacebuilding process and the possibility of considering them as the main actors of this process in Ukraine are analyzed. The main problems that may interfere with the effective work of non-governmental organizations are described. The functions performed by non-governmental actors and the prospects for their further work, as well as the methods that actors use to build the world, are highlighted. Organizations of different levels and areas directly working in the sphere of peace-building in Ukraine today are analyzed. The specific problems arising in Ukraine in the work of non-governmental organizations in the field of post-conflict peacebuilding are analyzed. Prospects for further research of the chosen topic are formed.